Comparison of MRSASelect Agar, CHROMagar Methicillin-Resistant Staphylococcus aureus (MRSA) Medium, and Xpert MRSA PCR for Detection of MRSA in Nares: Diagnostic Accuracy for Surveillance Samples with Various Bacterial Densities - Wolk, D. M. (American Society for Microbiology (ASM), 2009)
Rapid laboratory methods provide optimal support for active surveillance efforts to screen for methicillin-resistant Staphylococcus aureus (MRSA). Most laboratories struggle to determine the optimal use of resources, considering options to balance cost, speed, and diagnostic accuracy. To assess the performance of common methods, the first comparison of MRSASelect agar (MS) and CHROMagar MRSA (CA), with and without broth enrichment followed by a 24-h subculture to MS, was performed. Results were compared to those of the Xpert MRSA assay. For direct culture methods, the agreement between MS and CA was 98.8%. At 18 h, direct MS identified 93% of all positive samples from direct culture and 84% of those identified by the Xpert MRSA. For Trypticase soy broth-enriched MS culture, incubated overnight and then subcultured for an additional 24 h, the agreement with Xpert MRSA was 96%. The agreement between direct MS and Xpert MRSA was 100% when semiquantitative culture revealed a bacterial density of 2+ or greater; however, discrepancies between culture and Xpert MRSA arose for MRSA bacterial densities of 1+ or less, indicating low density as a common cause of false-negative culture results. Since 1+ or less was established as the most common MRSA carrier state, broth enrichment or PCR may be critical for the identification of all MRSA carriers who may be reservoirs for transmission. In this active-surveillance convenience sample, the use of broth enrichment followed by subculture to MS offered a low-cost but sensitive method for MRSA screening, with performance similar to that of Xpert MRSA PCR.